Pedagogical dilemma in teacher education: Bridging the theory practice gap - Phillips, H. N.; Condy, J. (South African Journal of Higher Education, 2023)
Purpose: The purpose of this study is to explore how teacher educators are preparing pre-service teachers to “learn from practice” which the policy on the minimum requirements for teacher education aspires to and which has its focus on campus-based teaching with the aim of narrowing the practice-theory divide. Design/methodology/approach: A qualitative approach through a phenomenological lens, provided opportunities for teacher educators, pre-service final year students and in-service teachers to share personal perspectives of their training experiences. Semi-structured and focus group interviews were specifically structured to solicit perceptions of the practical component of the course. Findings: Pre-service teachers feel that teacher educators are “out of touch” with what happens in classrooms and are not adequately trained to prepare them for the world of teaching. There is evidence that a misalignment exists between how training occurs on campus and what students are facing in the school classroom and this needs to be bridged. Campus courses should be carefully constructed and coordinated with field experiences to effectively guide and support student teacher learning. Originality: Empirical evidence is provided by the most eligible stakeholders i.e., teacher educators, pre-service teachers and in-service teachers, who were able to present their objective and practical views on the realities of their experiences with pre-service teachers’ preparedness to merge theory and practice successfully in a classroom.